Suicide by Caustic Chemicals Ingestion at Krathum Baen Hospital Samut Sakhon - Phongprapakorn, Pornchai (Journal of Health Science of Thailand, 2017)
This retrospective descriptive study was aimed to study patients who attempted suicide by caustic chemicals ingestion in Krathum Baen hospital from May 2005 to September 2007. It was found that 87 patients were male and female in a ratio of two to three (2:3) and mostly single. The average age was 26.72 years. Most of them were factory workers and were educated below secondary level. The length of stay in the hospital was one or two days usually on weekends. Admissions on Fridays, Saturdays and Sundays added up to 55 percent of the patients. Most of them were local people and the rest were migrant labours from other areas staying in rented accommodation. The result indicated that eighty of those attempted for the first time. The main factor caused them to attempt suicide was family conflicts. In addition female patients did it in contempt as a protest gesture. The minor factors were long term suffering from chronic illness and psychiatric problem. It was found that inappropriate treatments prevailed. Four percent of all patients were stimulated to vomit; 9.2 percent had no NPO, 66.7 percent did not receive any antibiotic drugs; 28.7 percent did not get acid reducing drugs; 42.5 percent did not have x - rays examination; 59.8 percent did not have esophagoduodenoscope examination, 58.6 percent were not provided with counseling with the psychiatric counselor and 92.0 percent did not have follow up treatment in community. As a result of the treatment; 91.5 percent of them had been well recovered and were allowed to go home, 6.9 percent refused to stay on and 1.1 percent or only one patient died. It also appeared that 86.1 percent of all patients avoided follow up treatment. Only one patient had esophageal stricture. Various treatments were continuously developed and analyzed to improve physical and mental outcomes.